Clinical presentation and pulmonary function tests in post-acute COVID-19 patients - Genzor, Samuel; Jakubec, Petr; Sova, Milan; Mizera, Jan; Joppa, Pavol; Burget, Radim; Pobeha, Pavol (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2023)
AIMS: The study analysed post-acute COVID-19 symptoms and the pulmonary function test (PFT) results in patients surviving the native strain of the virus. METHODS: The study was prospective; the inclusion criteria were positive PCR test for SARS-CoV-2 and age 18-100. Exclusion criteria were active respiratory infection, known or suspicious pre-existing pulmonary disease, cardiac failure, recent or acute pulmonary embolism, anaemia, and neuromuscular diseases. The recruitment period was 1st March 2020 - 25th December 2020. The initial examination was performed 4-12 weeks after the disease onset. All subjects underwent physical examination, anamnesis, chest x-ray and PFT. RESULTS: The study involved 785 subjects (345 male) mean age 53.8 (SD 14.6). The disease severity groups were: mild (G1), moderate (G2) and severe/critical (G3). Anosmia was present in the acute disease phase in 45.2% of G1 patients, but only in 4.5% of G3 patients. Dyspnoea occurred frequently in more severe groups (40%, 51.8% and 63.7% for G1, G2 and G3 respectively), while cough and fatigue showed no relationship to disease severity. Females were more likely to experience persistent symptoms. PFT results were significantly decreased in more severe groups compared to the mild COVID-19 patients, diffusing capacity was 86.3%, 79% and 68% of predicted values in G1, G2 and G3 respectively. CONCLUSION: Anosmia during the acute phase was associated with mild disease, persisting dyspnoea was more frequent after more severe COVID-19. Females tended to have persisting symptoms in post-acute phase more frequently. PFT results showed decrease with disease severity.
Keywords: dospělí; Female; SARS-CoV-2; dyspnoe; Adult; mladý dospělý; ženské pohlaví; Adolescent; lidé; Dyspnea; Aged, 80 and over; COVID-19; prospektivní studie; Male; Aged; Prospective Studies; Young Adult; Anosmia; lidé středního věku; Respiratory Function Tests; senioři nad 80 let; senioři; mužské pohlaví; respirační funkční testy; Middle Aged; mladiství; anosmie; Humans